Direct cold atmospheric plasma and plasma‐activated medium effects on breast and cervix cancer cells. Issue 11 (8th July 2020) - Jezeh, Mahya Aminrayai; Tayebi, Tahereh; Khani, Mohammad Reza; Niknejad, Hassan; Shokri, Babak
Abstract: In this study, the effects of cold plasma and plasma‐activated medium (PAM) are investigated through different treatment times, different intervals between treatment and analysis, and synthesis of helium gas and helium + 0.5% oxygen. The viability of two cancer cell lines including Hela and MDA‐MB‐231, which are related to cervix and breast cancers, respectively, is investigated using the 3‐[4, 5‐dimethylthiazol‐2‐yl]‐2, 5‐diphenyl tetrazolium bromide assay. To study the effect of plasma on normal cells, the corresponding method is used for examination of the normal human fibroblasts. H2 O2 showed a higher concentration after direct‐plasma treatment than PAM treatment. Caspase 3, caspase 8, and Bax proteins and the relative Bax/Bcl‐2 ratio are compared in both the direct‐plasma and PAM methods. The results show that the expression level of apoptotic proteins caspase 3 and caspase 8 in direct‐plasma treatment is higher than that in PAM treatment, and the level of relative Bcl‐2/Bax ratio is increased, demonstrating the induction of the apoptosis mechanism. Abstract : The effect of cold atmospheric plasma on the viability of cancer cells is evaluated through two separate methods including direct‐plasma treatment and plasma‐activated medium. In the first method, the cultured cancer cells are treated directly by cold plasma, whereas in the second, the cancer cells are exposed to the activated medium. We showed that direct‐plasma treatment stimulates the cells to the generation of higher amounts of H2 O2 and hence causes higher cell death. H2 O2 promotes cell death via apoptosis by stimulating the expression of the related genes.